A Vacuolar Membrane Ferric-Chelate Reductase, OsFRO1, Alleviates Fe Toxicity in Rice (Oryza sativa L.) - Li, Lin; Ye, Lingxiao; Kong, Qihui; Shou, Huixia (Frontiers in Plant Science, 2019)
Ferric reductase oxidase (FRO), the enzyme to reduce ferric iron [Fe (III)] into ferrous iron [Fe (II)], is known to play important roles in Fe absorption and homeostasis in strategy I plants, whereas there is no functional FROs in the typic Strategy II plants. Rice is able to use both strategies for Fe uptake depending on the growth conditions. There are two FRO genes in rice genome, but their function is yet characterized. Amino acid sequence alignment showes that OsFRO1 contains all necessary motifs for a functional FRO enzyme, whereas OsFRO2 lacks complete transmembrane domains in its N-terminal, thus likely is a pseudogene. Transient expression of OsFRO1: GFP protein fusion revealed that OsFRO1 is localized to the vacuolar membrane. OsFRO1 mainly expressed in leaves. And its leaf expression of OsFRO1 was down regulated under excessive Fe conditions. While transgenic plants overexpressing OsFRO1 exhibited more sensitive to Fe toxicity, RNA inteference lines showed more tolerance to Fe toxicity. Furthermore, RNAi lines showed decreased Fe concentrations compared to wildtype plants under Fe excessive condition. Based on the above data, we propose that OsFRO1 is involved in reducing ferric Fe into ferrous Fe in vacuole, and make the vacuolar stored Fe availible to cytoplasm through Fe (II) or chelated Fe (II) transporters. Under Fe excessive condition, the downregulation of OsFRO1 in the RNAi plants reduced the amount of Fe (II) availible for cytoplasm, and therefore alleviates Fe excessive toxicity. Our results shed new light on developing new rice varieties with enhanced ability to thrive on high-Fe soils as well as deepening understanding of Fe metabolism in plants.